Types and Factors of Code-Switching in Deddy Corbuzier’s Podcast - Yulia Mutmainnah (Universitas Muhammadiyah Semarang, 2022)
With the increasingly sophisticated technology, especially in the field of communication, and the ease with which people can mobilize from one area to another, the phenomenon of code-switching has become a very common thing, including the conversation between Deddy Corbuzier and Agnez Monica in a Deddy Corbuzier’s podcast on the YouTube channel entitled